Identification of PCBP1 as a Novel Modulator of Mammalian Circadian Clock - Wu, Yaling; Zhao, Haijiao; Zhang, Eric Erquan; Liu, Na (Frontiers in Genetics, 2021)
The circadian clock governs our daily cycle of behavior and physiology. Previous studies have identified a handful of core clock components and hundreds of circadian modifiers. Here, we report the discovery that PCBP1, displaying a circadian expression pattern, was a novel circadian clock regulator. We found that knocking down PCBP1 resulted in period shortening in human U2OS cells, and that manipulations of PCBP1 expression altered the activity of CLOCK/BMAL1 in an E-box-based reporter assay. Further mechanistic study demonstrated that this clock function of PCBP1 appears to work by enhancing the association of CRY1 with the CLOCK/BMAL1 complex, thereby negatively regulating the latter's activation. Co- immunoprecipitation of PCBP1 and core clock molecules confirmed the interactions between PCBP1 and CRY1, and a time-course qPCR assay revealed the rhythmic expression of PCBP1 in mouse hearts in vivo. Given that the RNA interference of mushroom-body expressed (mub), the PCBP homolog of Drosophila, in the clock neurons also led to a circadian phenotype in the locomotor assay, our study deemed PCBP1 a novel clock modifier whose circadian regulatory mechanism is conserved during evolution.